290 Impacts of dietary zinc concentrations on lamb feedlot performance. (30th November 2020) - Knuth, Ryan; Cunningham, Hannah; Bangooura, Berit; Julian, Alexis; Page, Chad M; Hummel, Gwendolynn; Woodruff, Kelly; Whaley, Jaelyn; Bardsley, Katherine; Lake, Scott; Gifford, Cody; Bisha, Bledar; et al.
Abstract: The objectives of this study were to identify the impacts of Zn concentrations in lamb grower pellet on lamb feedlot performance and natural coccidia infection in terms of fecal Eimeria oocyst excretion. Rambouillet lambs (n = 33; 43.9 ± 1.0 kg) were used in a 63 d feeding trial to assess the effect of a diet fortified with a combination of ZnSO4 (80%) and Zn amino acid complex (20%; ZnAA; Zinpro Corp.; Eden Prairie, MN, USA) at three different dietary Zn concentrations (treatment, TRT) which met or exceeded current recommendations. These levels included 1×NRC requirements (450 mg/kg grower pellet; 1NRC), 2×NRC requirements (900 mg/kg grower pellet; 2NRC), and 3×NRC requirements (1350 mg/kg grower pellet; 3NRC). Lamb performance characteristics, including body weight (BW), average daily gain (ADG), average dry matter intake (DMI), feed efficiency (gain:feed, G:F), and residual feed intake (RFI), were quantified. Fecal samples were collected every 2 wk to assess coccidia infection status via fecal oocyst counts. Treatment × period (d 0–10, 11–42, 42–63) interactions were identified for DMI (P < 0.001). No main effect of TRT was identified for BW, ADG, G:F, or RFI (P > 0.36), but was for DMI (P = 0.02). Ten Eimeria species were detected and summed for total fecal oocyst count, but focus was on the most pathogenic species (E. ahsata, E. bakuensis, E. crandallis, and E. ovinoidalis). A statistical tendency for the interaction between TRT × day was detected for E. bakuensis and E. ovinoidalis (P ≤ 0.08). Transformed counts of E. bakuensis and E. crandallis were lower for 1NRC compared to 2NRC and 3NRC lambs (P < 0.05). Results indicate greater dietary Zn concentrations increased DMI and decreased Eimeria oocysts excreted.